Open Science practices in a Portuguese nursing higher education institution: An exploratory, descriptive study - Ana Sabrina Sousa; Mafalda Lopes; Diana Rodrigues; Palmira Oliveira; Regina Pires; Sara Pinto; Pedro Melo; João Frias Rosa; Amparo Alves; Rosa Silva (PLoS ONE, 2025)
Open Science has emerged as an epistemological paradigm that promotes open and dynamic access to knowledge, fostering the sharing of scientific findings, collaboration between academia and society, and enhancing innovation and transparency. However, comprehensive studies on the adoption of Open Science practices remain limited, particularly in the nursing academic context. This study aimed to identify the current Open Science practices within a Portuguese higher nursing education institution community. An exploratory, descriptive study was conducted in two phases. In the first phase, a questionnaire was adapted and piloted through a focus group. In the second phase, the final version of the questionnaire, with 34 questions, was distributed digitally to 747 teachers, researchers and students. The study included 35 respondents, predominantly faculty members. While 77.8% reported engaging with Open Science publications, fewer respondents demonstrated familiarity with practices such as study preregistration and open-source coding. The principles of Open Science were widely accepted, particularly those emphasizing ethics, the democratization of knowledge, and scientific collaboration. Participants frequently used tools like EBSCOhost, Medline, and Scopus, whereas platforms such as Zenodo and OpenUP Hub remained underutilized. Participants highlighted training priorities, especially in open access publishing, data management, and the implementation of Open Science recommendations. The low response rate may indicate limited awareness of Open Science among professionals and an institutional culture in which such practices have not been fully embedded within academic routines. Although all participants agreed with the principles of Open Science, most reported not knowing its policies and not all were familiar with the various formats. These findings underscore the importance of investing in skills training and raising awareness of Open Science practices, particularly within the nursing school context. Furthermore, they underscore the need for in-depth investigation into the motivations, barriers, and enabling conditions that influence adherence to Open Science in higher education.